Tonga : 2015 Article IV Consultation-Staff Report; and Press Release. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Tonga's economy is estimated to have grown by about 2 percent in FY2013/14 (year ending June) driven by agriculture and construction, following a contraction in 2012/13 mainly caused by the completion of a large capital project. The external position has strengthened, following large grants and remittance inflows, which have bolstered international reserves. Real GDP growth is expected to average 2-3 percent in FY2014/15-FY2019/20. Although the progress of reconstruction in the aftermath of 2014 Cyclone Ian is slower than expected, the coronation scheduled for July 2015 and preparations for the 2019 South Pacific Games will support economic activity over the next few years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet